Relationship between Environmental Sanitation and Incidence of Diarrhea among Children Under Five in Alak Health Center, Kupang, East Nusa Tenggara - Dahniar Salsabiella Djaba; Johny A. R Salmun; Amelya Betsalonia Sir (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Diarrhea is an occurrence of mushy to liquid bowel movements, with a frequency of 3 times or more in a day. Diarrhea is influenced by several factors that directly or indirectly include agent, host, and environmental factors. Environmental sanitation factors are the most dominant factors causing diarrhea, namely drinking water sources, latrine conditions, garbage disposal conditions, and waste drain conditions. Alak Community Health Center is one of the community health centers with the highest cases of diarrhea with a total of 557 cases in 2018, 428 cases in 2019, and 296 cases in 2020. This study aims to determine the correlation between environmental sanitation and the incidence of diarrhea in children under five in the working area of the Alak Community Health Center, Kupang City. Subjects and Method: A quantitative study with a cross-sectional design conducted in the working area of the Alak community health center, Kupang, East Nusa Tenggara in November-December 2022. A total of 93 children under five were selected by simple random sampling. The dependent variable was the incidence of diarrhea in children under five. The independent variables were raw water sources, latrine conditions, garbage disposal conditions, and wastewater disposal conditions. The data were collected using questionnaires and analyzed using chi-square tests. Results: There was a significant association between raw water sources (p< 0.001), latrine conditions (p< 0.001), landfills (p< 0.001), and wastewater disposal (p= 0.001) to the incidence of diarrhea in children under five. Conclusion: There is a correlation between raw water sources, latrine conditions, garbage disposal, and wastewater disposal to the incidence of diarrhea in children under five. Keywords: diarrhea, environmental sanitation, children under five. Correspondence: Dahniar Salsabiella Djaba. Faculty of Public Health Universitas Nusa Cendana Kupang. Lasiana, Lima, Kupang, East Nusa Tenggara, Indonesia. Email: dahniarsalsabielladjaba@gmail.com. Mobile: +62 812-3909-5885.